Pengaruh Makna Gedung Gereja terhadap Motivasi Partisipasi dalam Pembangunan dengan Mediasi Persepsi Kemegahan Gereja - Nasila, Meri Ervi Yana; Lefran, Lefran; Parinsi, Niel Kapoginta (Sekolah Tinggi Agama Kristen Luwuk Banggai, 2024)
This study examines the influence of the meaning of church buildings on the congregation's motivation in the construction of church buildings at the Betesda Paisubatango Congregation. The general phenomenon observed is the tendency of Christian communities to build large and grand church buildings, despite often facing financial constraints. This study uses a quantitative method with a survey approach. The sample for this study consists of 30 adult congregants from the Betesda Paisubatango Church. The results show that the meaning of the church building has a positive influence on the congregation's motivation to participate in the construction of the church building. The higher the meaning of the church building for the congregation, the higher the congregation's motivation to be involved in the construction of the church building. However, the concept that the church building must be large and grand does not strengthen the influence of the meaning of the church building on the congregation's motivation to participate in the construction of the church building.